2018
DOI: 10.1002/nau.23762
|View full text |Cite
|
Sign up to set email alerts
|

Transsynaptic tracing to dissect supraspinal serotonergic input regulating the bladder reflex in rats

Abstract: The caudal subsets of RN, especially the raphe magnus, are the main sources of serotonergic input to the lower spinal cord controlling bladder activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…These mainly include the pontine micturition center/Barrington's nucleus, the periaqueductal gray, the hypothalamus, and the motor cortex (Andersson and Arner, 2004;Nadelhaft and Vera, 2001;Verstegen et al, 2019;Yao et al, 2019). The descending reticulospinal projections were severely affected by the SCI, resulting in a large decrease of spinal coverage below the level of the lesion including the CRF-positive fibers originating in the pontine micturition center, the main nucleus responsible for voiding initiation, as well as 5-HT-positive fibers from the raphe system (Ahn et al, 2018). 5-HT fibers regulate the level of excitation in different spinal circuits; they facilitate the urinary guarding reflex by inhibiting the parasympathetic pathway that causes detrusor contraction (Chang et al, 2007;Khaled and Elhilali, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…These mainly include the pontine micturition center/Barrington's nucleus, the periaqueductal gray, the hypothalamus, and the motor cortex (Andersson and Arner, 2004;Nadelhaft and Vera, 2001;Verstegen et al, 2019;Yao et al, 2019). The descending reticulospinal projections were severely affected by the SCI, resulting in a large decrease of spinal coverage below the level of the lesion including the CRF-positive fibers originating in the pontine micturition center, the main nucleus responsible for voiding initiation, as well as 5-HT-positive fibers from the raphe system (Ahn et al, 2018). 5-HT fibers regulate the level of excitation in different spinal circuits; they facilitate the urinary guarding reflex by inhibiting the parasympathetic pathway that causes detrusor contraction (Chang et al, 2007;Khaled and Elhilali, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Several reports also suggest GABAergic projections from RVM to spinal dorsal horn as direct input to postsynaptic neurons such as spinal interneurons and ascending projection neurons (Aicher et al., 2012; Hossaini et al., 2012; Kato et al., 2006; Reichling & Basbaum, 1990). PRV tracing from the bladder demonstrated that bladder‐specific serotonergic RVM neurons are mostly expressed in the caudal raphe with the highest number in the RMg (Ahn et al., 2018). Similarly, our PRV‐tracing experiments have demonstrated that about 14% of RVM neurons connected to the bladder are TpH2 positive with major expression in RMg, Gi, and LpGi nuclei.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has also shown that bladder-projecting neurons in the caudal raphe nucleus, the area of the brainstem which exhibits supraspinal control of the bladder, also express serotonin (Ahn et al 2018), suggesting that serotonergic control of the bladder could have both peripheral and central components which involve the 5-HT 3 receptor.…”
Section: -Ht Has a Direct Effect On Afferent Firing Via The 5-ht 3 Re...mentioning
confidence: 99%